DIFFERENCES IN HEMOGLOBIN LEVELS WITH SIT AND SITTING BLOOD DRAWINGS TECHNIQUES - Salsabila, Masayu Putri; Utari, Veny Tresia; Sari, Indah; Bastian, Bastian (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Introduction – Blood is one of the most important organts in human body. Blood samples are usually obtained by drawing blood in a vein known as phlebotomy. Blood specimen collection generally can be done with various postures including lying on a bed or sitting down. Patient should sit comfortably in a suitable chair or lying down when taking blood because posture can cause significant changes in blood cell components such as hemoglobin. Purpose – This research aims to determine whether there's a difference between hemoglobin levels with sitting and lying blood sampling techniques Methodology/Approach – The type of research used is comparative cross-sectional, conducted at the Hematology Laboratory IKesT Muhammadiyah, Palembang. Samples were taken from 30 respondents who entered the inclusion criteria. The research results were processed using Statistical Product and Service Solution(SPSS) program. Research data on differences in hemoglobin levels with the sitting and lying blood sampling technique were analyzed using the Dependent T test. Findings – The average of hemoglobin level in sitting position obtained was 12,7mg/dL, while in the lying position was 12,3mg/dL. The result of the dependent-t test, it was known the signature value was P=0,000. The P value obtained is <0,05, so it can be concluded that there's a significant difference between sitting and lying blood sampling techniques. Originality/ Value/ Implication – Difference between this research and other is that using a comparative cross-sectional method where the data processed using SPSS program. The component researched were also different, namely the hemoglobin levels.